The Analysis of Determinants of Public Junior High School Teacher Performance in Semarang - Setianah, Widi; Pramono, Suwito Eko; Wahyudin, Agus (Proceedings of International Conference on Science, Education, and Technology, 2025)
Teacher performance is still low. Many factors affect teacher performance, both internal and external. Many theories explain the relationship between these factors and teacher performance. The purpose of this study is to determine the determination of teacher performance, which is related to leadership style through job satisfaction and moderated by work commitment to the performance of public junior high school teachers in Semarang. This study uses a quantitative approach and the type of research is correlational research. The population of the research are 3.646 teachers and the sample of this study are 360 junior high school teachers in Semarang. The determination of the sample uses proportional random sampling. The dependent variable of the study is teacher performance. The intervening variable is job satisfaction, the moderating variable is work commitment and the independent variable consists of leadership style. The data collection technique uses an instrument in the form of a questionnaire. The data analysis technique uses validity test, reliability test, classical assumption test, simple and multiple regression analysis, coefficient of determination, hypothesis test and path analysis. The results shows that there is a significant direct influence between Leadership style (X) has a positive effect on teacher performance (Y). There was a significant direct influence that leadership style (X) has a positive effect on teacher job satisfaction (M). Leadership style (X) has an indirect effect on teacher performance (Y) through teacher job satisfaction (M). Organizational commitment (R) moderates indirectly between teacher job satisfaction (M) and teacher performance (Y). Research suggestions a) are expected to be able to develop or add indicators to the leadership style variable on teacher job satisfaction and performance in this study, b) This research model can be developed to improve teacher performance, especially leadership style, job satisfaction and work commitment in junior high school teachers in Semarang.